The prevalence, associated factors, and the burden on health state utilities for dementia in Chile: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - Zitko, Pedro; Slachevsky, Andrea; Jimenez, Daniel
Abstract: Background: New procedures based on attributional methods have not been used to estimate the burden of Dementia in term of loss of Health‐State Utilities (HSU) or Quality‐Adjusted Life Years (QALY) at the populational level. Chile, in recent decades, has presented an accelerated aging process and has few studies on dementia. Method: We analysed data from the Chilean National Health Survey carried out between 2016‐2017 (n=5, 004). Participants older than 59 years were screened for dementia, defined by a score higher than 5 in the Pfeffer and lower than 13/19 points in a modified MMSE‐version, previously validated in Chile. HSU were measured using the health‐related quality of life instrument EQ5D plus national values for utilities for each health state. The number and fraction of total HSU lost due to dementia were calculated using attributable fraction methods. We repeated the procedure on each one of five domains of EQ5D. Factors associated with dementia were explored using a logistic regression model. Other comorbidities (depression, chronic musculoskeletal pain, hypertension, diabetes) were included in the models. Result: We estimated a prevalence of 4.4% [2.9‐5.9] for dementia in people older than 59 years. Dementia, compared with other comorbidities, showed the highest loss of HSU, accounting 38.3 [26.0‐50.6] additional points of loss of HSU over the score from those without dementia (where 0 means healthy, and 100 is equivalent to death). Prevalent cases of dementia were associated with a loss of 41, 046 QALYs [29, 727 – 52, 158], which was equivalent to a 5.0% [3.0‐7.6] of total burden among elderlies, and 1.5% [0.9‐2.4] in the population older than 14 years. 'Self‐care' was the domain were dementia accounted higher burden followed by 'usual activities' (see figure). Age was associated with dementia, while male sex, lower education, widower compared with married, and some comorbidities showed high OR but without reaching statistical significance. Conclusion: Dementia at the population level showed a high impact in terms of QALY lost, as well as at the individual level in terms of loss of HUS, overpassing to other diseases. Key domains of quality of life affected higher for Dementia were self‐care and usual activities. FONDAP Program Grant 15150012.